Pengaruh Media Pendidikan Gizi Mengenai Pentingnya Konsumsi Ikan Terhadap Tingkat Pengetahuan Siswa Di SMK Hang Tuah 1 Jakarta - Syifa Mulia Rahma, (2021)
The statistic of consuming fish in Indonesia still lower than other countries because mostly people here doesn't have a good knowledge of the matter in its nutrient and the advantages by consuming fish. The educational media that contain words and pictures alike booklets and comics are able to use to distract teenager attention and keep them from tedium of reading. This study aims to determine the effect of nutritional education media such booklets and comics about the importance of fish consumtion to knowledge meter in SMK 1 Hang Tuah Jakarta. This research was quasy experimental with pretest posttest control group design. The study was conducted on 126 samples at SMK 1 Hang Tuah Jakarta. The statistical test used paired t-test and independent t-test. The results showed the influence of media booklets and comic to the knowledge about how important to consume fish before and after intervention using booklets (p=0,000) & comics (p=0,000) at SMK 1 Hang Tuah Jakarta. There was not significant differences in nutrition knowledge about how important to consume fish using booklets and comics (p>0.05). There is an effect of nutrition education using comic and booklet about how important to consume fish for the knowledge of students SMK 1 Hang Tuah Jakarta.